(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Products made of thermally treated wood have different requirements for the quality of the created surface, depending on the area of their application. While we can make do with a milled surface for tiling and flooring, we have more sophisticated products such as garden furniture, etc. require final surface sanding. The article focuses on the effect of thermal modification on the quality of the ground surface. It compares the surface quality of the ground surface of native woods oak, spruce and meranti with their thermally treated variants at temperatures of 160°C, 180°C, 200°C and 220°C. Quality is examined on a surface sanded with a belt sander with 80-grit sandpaper. It points to the fact that the process of thermal modification slightly impairs the quality of the ground surface. However, when evaluating a surface on a larger scale, the quality of the created surface is influenced mainly by the "natural roughness of the wood" by the opening of anatomical elements of the wood, which are the primary source of increased roughness.